Control and Data Communication Required for Hierarchical Control of Future Smart Microgrids - Setiawan, I Made Andik (Curtin University, 2017)
This thesis proposes and discusses a required hierarchical data communication network for Microgrid, a new technique for simultaneous voltage regulation and power/current sharing in dc Microgrid, Various Microgrids configurations and their effects on the proposed technique, a new algorithm for establishing the shortest data communication, and the proposed centralized and decentralized data communication schemes for Microgrid applications. All proposed and discussed algorithms/methods are numerically analysed and simulated via digital software in PSCAD/EMTDC and Matlab Simulink.